Clinicopathological findings and disease staging of feline infectious peritonitis: 51 cases from 2003 to 2009 in Taiwan - Tsai, Hsien-Ying (J Feline Med Surg, 2011)
Fifty-one cats histopathologically confirmed to have been naturally infected by feline infectious peritonitis (FIP), were collected to analyse the clinical and laboratory findings and to characterise disease staging. Effusive FIP was found in 33 cats, non-effusive FIP in 12 cats, and mixed-type in six cats. Highly significant decreases in haematocrit and albumin levels and an increase in total bilirubin level were noted in both effusive and non-effusive FIP, at first presentation and before death. In serial blood examinations of the effusive group, anaemia and increases in bilirubin and aspartate aminotransferase (AST) were observed from 2 weeks to 0–3 days before death. The packed cell volume, bilirubin, AST, potassium, and sodium levels were established to predict disease staging and survival time. Cumulative points ranging from 0 to 4, 5 to 11 and excess of 12, indicate that the cat can survive for at least 2 weeks, less than 2 weeks and less than 3 days, respectively.